Kenya Economic Update, April 2017, No. 15 : Housing - Unavailable and Unaffordable - World Bank Group (World Bank, Washington, DC, 2017)
Economic activity in Kenya remained robust in 2016. For the third consecutive year economic activity in Kenya picked-up, reaching an estimated 5-year high of 5.9 percent in 2016, once again placing Kenya among the fastest growing economies in Sub-Saharan Africa. Kenya's growth momentum in 2016 was supported by a stable macroeconomic environment, low oil prices, favorable harvest in the first half of 2016, rebound in tourism, strong remittance inflows, and an ambitious government infrastructure drive to relieve supply side constraints. Near term GDP growth is expected to dip on account of headwinds, however over the medium term GDP growth should pick-up. Given headwinds from the ongoing drought, weak credit growth, and the pick-up in oil prices, GDP growth is expected to decelerate to 5.5 percent in 2017, a 0.5 percentage point mark down from earlierforecasts. However, over the medium term, we expect these headwinds to ease (rains are expected to return to normal in 2017), and together with the projected steady strengthening of the global economy, rebound in tourism, resolution of some of the underlying causes of slow credit growth, and the easing of some supply-side constraints related to the completion of some major infrastructure projects, GDP growth is expected to accelerate to 5.8 percent and 6.1 percent in 2018 and 2019 respectively, consistent with the underlying growth potential of the Kenyan economy.